2020
DOI: 10.1002/jsfa.10244
|View full text |Cite
|
Sign up to set email alerts
|

Botanical and geographical origin of Turkish honeys by selected‐ion flow‐tube mass spectrometry and chemometrics

Abstract: BACKGROUND Honey has a very important commercial value for producers as a natural product. Honey aroma is formed from the contributions of several volatile compounds, which are influenced by nectar composition, botanical origins, and location. Selected‐ion flow‐tube mass spectrometry (SIFT‐MS) is a technique that quantifies volatile organic compounds simply and rapidly, even in low concentrations. In this study, the headspace concentration of eight monofloral (chestnut, rhododendron, lavender, sage, carob, hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…Several analytical techniques, mainly based on nuclear magnetic resonance [5,14,15], Raman and infrared spectroscopy [16,17], mass spectrometry [18][19][20], electronic tongue [21,22] and electronic nose [23,24], in combination with chemometrics, have been applied to discriminate the geographical origin of honey.…”
Section: Introductionmentioning
confidence: 99%
“…Several analytical techniques, mainly based on nuclear magnetic resonance [5,14,15], Raman and infrared spectroscopy [16,17], mass spectrometry [18][19][20], electronic tongue [21,22] and electronic nose [23,24], in combination with chemometrics, have been applied to discriminate the geographical origin of honey.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported change of protein values of honey samples between 0.33% and 1.2% (Azeredo et al, 2003;Ozcan-Sinir et al, 2020;Ozcan & Olmez, 2014). Honey contains low amounts of amino acids, and proline is a major component (Serra Bonvehí & Escolà Jordà, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the composition of honey depends on not only the diversity of flowers but also some other factors such as environmental factors, harvesting climate, processing, and storage technology (Kaškonienė & Venskutonis, 2010;Ozcan-Sinir et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The volcano plot and HCA between two geographical origins clearly illustrated that samples from distant meliponiculture sites (Pulau Pinang and Perak) have better clustering (no mixing of samples from different origins) and a higher number of up‐ and downregulated compounds. Although stingless bees of similar entomological origin are responsible for the production of honey at these two places, the floral origin, nectar composition, and surrounding environmental factors significantly vary at distant distance, contributing to significant difference (Ozcan‐Sinir et al., 2020). However, for nearer meliponiculture sites (Pulau Pinang with Perak and Pulau Pinang with Kedah), there were variations in terms of volatile organic compounds and their compositions, but not as much compared to distant meliponiculture sites.…”
Section: Resultsmentioning
confidence: 99%